Prevention of infections associated with peripheral catheters: construction and validation of clinical scenario - Raissa Silva Souza; Patrícia Peres de Oliveira; Ana Angélica Lima Dias; Delma Aurélia da Silva Simão; Aline Eloá Barbosa Pelizari; Rosely Moralez de Figueiredo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to describe the process of construction and content validation of a clinical setting for teaching and learning the recommended practices for preventing bloodstream infection, associated with peripheral venous catheters, for nursing professionals. Methods: methodological study of the construction of the scenario based on the National League Nursing Jeffries Simulation Theory, International Nursing Association for Clinical Simulation and Learning, and the Brazilian Health Regulatory Agency. Twelve experts performed content validation. We used to assess the degree of agreement between them, the Content Validity Index, and a descriptive analysis of the suggestions presented. Results: all the requirements of the simulated clinical scenario reached an agreement between judges of more than 80% in terms of clarity and relevance. Conclusions: the steps adopted in the construction and validation of the clinical scenario proved to be adequate and relevant, and the scenario is suitable for training professionals.